Evaluation of Accountability Measurement Tool in Patients with Psoriasis: A Validation Study - Jennifer J. Su; Abigail Cline; Arjun M. Bashyam; E. J. Masicampo; Edward H. Ip; Steven R. Feldman (Adis, Springer Healthcare, 2020)
Abstract Introduction The role of accountability in promoting patient adherence to medication is not well characterized. An accountability measurement tool (AMT) has been developed to quantify accountability but has not been investigated for use with patients with skin disease. We aim to test the reliability and validity of the AMT for patients with psoriasis. Methods A 12-item AMT was used for patients with psoriasis. English-speaking adults with psoriasis who were expected to continue their medication were asked to complete the questionnaire. Reliability was measured using Cronbach's alpha. Validity was measured using Pearson's correlation coefficient and t-tests between the AMT and other validated scales measuring fear of negative evaluation and self-regulation. Results A total of 30 patients were recruited for this study. The AMT demonstrated excellent internal consistency (Cronbach's $$α$$ α = 0.86). Total accountability positively correlated with fear of negative evaluation (r = 0.59), autonomous motivation (r = 0.46), introjected regulation (r = 0.60), and external regulation (r = 0.57), demonstrating good convergent validity. Divergent validity was supported by nonsignificant associations between psoriasis accountability and age, gender, race, education level, years with physician, and amotivation. Conclusions The AMT has been further validated for measuring accountability in patients with psoriasis.